Experimental study to evaluate the effect of particle size on the small strain shear modulus of coarse-grained soils. (15th October 2020) - Liu, Xingyang; Zou, Degao; Liu, Jingmao; Zhou, Chenguang; Zheng, Bowen
Highlights: We conducted shear wave velocity tests using a newly developed device. We measured the particle morphology based on Fourier analysis method. The small strain stiffness is insensitive to mean particle size for uniform soil specimens. The small strain stiffness increases with mean particle size for well-graded soil specimens. Abstract: Coarse-grained soils are found commonly in nature and are extensively used for a wide range of engineering applications, such as slopes, earth dams, and railway foundations. This study presents an experimental investigation on the effect of mean particle size D 50 on the small strain shear modulus G max of coarse-grained poorly-graded and well-graded soils. Combined with particle morphology analysis, a series of shear wave velocity tests were performed on pure sand, pure gravel and sand-gravel mixture specimens by taking advantage of a torsional vibration measurement device in a large scale triaxial apparatus. The results demonstrate that G max is insensitive to D 50 for uniform sand and gravel specimens. On the other hand, G max increases gradually with D 50 for well-graded sand-gravel mixture specimens. The discrepancy in the relationship between G max and D 50 for poorly- and well-graded soils is related to the degree of size polydispersity in the specimens.